Art music in Serbia as a political tool and/or refuge during the 1990s - Milin, Melita (Muzikološki zbornik, 2011)
The focus of the article is on Serbian composers' responses to the turbulent political developements and wars during the last decade of the 20th century in ex-Yugoslavia. Both their creative work and political activism are considered. There was a general mistrust that art music could make a strong impact on political events, so that composing was mainly felt to be a refuge from brutal reality. Certain authors, however, expressed protest through their works, usually in indirect ways.
Keywords: 20.st.; 20th cent.; glasba in politika; glasba in vojna; music and politics; music and war; Serbian art music; srbska umetna glasba